Vitamin D - Not Just a Simple Vitamin - Nasim Karim; Talea Hoor (Journal of Bahria University Medical and Dental College)
Vitamin D refers to a group of fat-soluble secosteroids responsible for enhancing intestinal absorption of calcium, iron, magnesium, phosphate and zinc. In humans, the most important compounds in this group are vitamin D3 and vitamin D2.Very few foods contain vitamin D. Synthesis of vitamin D (specifically cholecalciferol) in the skin is the major natural source of the vitamin. Dermal synthesis of vitamin D from cholesterol is dependent on sun exposure. Vitamin D deficiency is said to be associated with osteoporosis, type 2 diabetes, rickets, psoriasis, depression, schizophrenia, cancers, obesity etc. Vitamin D deficiency is wide spread in South Asian especially in Pakistani population and is contributing to burden of disease in this region. It is suggested that vitamin D supplementation program may be undertaken by the government on mandatory basis.